Green-eyed demon - Wells, Jaye (Sabina Kane ;, 2011)
"The clock is ticking for Sabina Kane. Her sister has been kidnapped by her grandmother, the Dark Races are on the brink of war, and a mysterious order is manipulating everyone behind the scene. Working on information provided by an unlikely ally, Sabina heads to New Orleans to begin the hunt for her sister. Once there, she must contend with belligerent werewolves, magic-wielding vampires, and--perhaps most frightening of all--humans. But as much as Sabina is focused on surviving the present, the past can't be ignored. Before she can save those she cares about most, she must save herself from the ghosts of her past."--P. [4] of cover.